The relationship between exercise addiction and depression of elite athletes during quarantine and closure of sports venues and events due to Corona virus (Covid-19) - Ghabel Damirchi, B.; Dabbagh, H.; Khanjani, G.; Gharayagh Zandi, H. (Journal of Motor and Behavioral Sciences, 2020)
Introduction & Purpose: The present study aimed at investigating the relationship between exercise addiction and depression of athletes and closure of sports venues and events due to corona virus (Covid-19). Methodology: The current study was a descriptive correlational one. The participants of the study consisted of 134 elite athletes (64 men) who had at least 5 years of sports experience at the level of the super league and national with an average age of 20.87 (15 to 35 years). To measure exercise addiction, exercise addiction checklist of Terry et al. has been applied, and Beck`s depression questionnaire has been used to measure the depression. The collected data has been analyzed by means of Spearman's correlation coefficient and regression. Results: The results of the study revealed no significant relationship between exercise addiction and depression. However, not only there is a negative significant relationship between the importance and prominence of the role of exercise with depression, but also it significantly predicted depression (p Conclusions: According to the findings, during quarantine due to Covid-19, with decreasing importance and prominence of the role of exercise, depression of athletes will be increased. Moreover, the importance and prominence of the role of exercise was a predictor of depression and athletes also show depression symptoms atypically.